THE IMPACTS OF STOCK LIQUIDITY ON DIVIDEND POLICY: EVIDENCE FROM LISTED FIRMS ON HOCHIMINH STOCK EXCHANGE - Phùng Đức Nam; Hoàng Thị Phương Anh; Lê Thị Thanh Vương (Tạp chí Khoa học Đại học Đà Lạt)
This study investigates the relationship between stock liquidity and corporate dividend policy of 267 listed firms on the Hochiminh Stock Exchange during the period from 2008 to 2016. The empirical results statistically indicate a significant negative relationship between stock liquidity and dividend policy in the context of Vietnam. This means that when a company has a stock with high liquidity, there will be a high possibility that the company will not pay out dividends or pay no dividends.